Investigation on the Antimicrobial Effect of Rodalon on Some Pathogenic Microbes Observed on Silken Fibers - Ashjaran, A.; Ghazi-saeidi, R.; Khajavi, R.; Rashidi, A.; Sattari, M. (Asian Journal of Chemistry, 2010)
In Iranian culture, carpet is the most common first choice for covering the floor. It is a very suitable substrate for growing pathogenic microbes. In present research, the main aim is to investigate the antibacterial effectiveness of Rodalon solutions on silken fibers by spraying method used in silken carpet. Silken pile carpet laid in a public place (in VIP of The Homa hotel) for 30 days and the existence of some microbes were investigated on it. The antimicrobial effect of different Rodalon solutions for identified microbes was studied in vitro. The silken fibers were treated with the same different solutions of Rodalon as before and the antimicrobial effectiveness was assessed by the zone of inhibition method in different times. Two pieces of carpet untreated and treated with Rodalon solution sewed together and laid for two weeks in the public same place and the amounts of bacterial growth determined by colony count method and the results compared. Finally some mechanical properties of treated silken fibers measured after 30 days and compared with untreated one. The results showed the presence of some pathogenic microbes on the laid carpet such as Escherichia coli and Staphylococcus aureus. The inhalation time for treated silken fibers improved. The amount of colony growth on treated carpet reduced considerably and besides the mechanical tests results showed no significant deterioration effect of studied properties in comparing with untreated yarn.